2013
DOI: 10.1002/ece3.650
|View full text |Cite
|
Sign up to set email alerts
|

Combining molecular evolution and environmental genomics to unravel adaptive processes of MHC class IIB diversity in European minnows (Phoxinus phoxinus)

Abstract: Host-pathogen interactions are a major evolutionary force promoting local adaptation. Genes of the major histocompatibility complex (MHC) represent unique candidates to investigate evolutionary processes driving local adaptation to parasite communities. The present study aimed at identifying the relative roles of neutral and adaptive processes driving the evolution of MHC class IIB (MHCIIB) genes in natural populations of European minnows (Phoxinus phoxinus). To this end, we isolated and genotyped exon 2 of tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 109 publications
(224 reference statements)
0
17
0
Order By: Relevance
“…Examples of the latter include the use of 16S rDNA denaturing gradient gel electrophoresis (DGGE) and clone sequencing to suggest that vector gut microbiota may influence transmission and virulence of Trypanosoma cruzi [92], similar methods used for understanding gut microbiota assembly in the western corn rootworm (Coleoptera) and their potential as pathogen vectors [93], variation in bumble bee gut bacteriome between related species and how this varies with pathogen infections [94], and the suggestion via metatranscriptome sequencing that shifts in honey bee gut bacteria/community may be a marker of CCD [86]. Pathogens in the microbiotic environment in which organisms live are also important for health and as selective agents: metabarcoding of bacterial communities local to European minnow populations has shown that host-parasite interactions drive local adaptation of the major histocompatibility complex (MHC) class IIB loci, in relation to local pathogen diversities [95].…”
Section: Potential For Development Of Edna Methods In Parasitologymentioning
confidence: 99%
“…Examples of the latter include the use of 16S rDNA denaturing gradient gel electrophoresis (DGGE) and clone sequencing to suggest that vector gut microbiota may influence transmission and virulence of Trypanosoma cruzi [92], similar methods used for understanding gut microbiota assembly in the western corn rootworm (Coleoptera) and their potential as pathogen vectors [93], variation in bumble bee gut bacteriome between related species and how this varies with pathogen infections [94], and the suggestion via metatranscriptome sequencing that shifts in honey bee gut bacteria/community may be a marker of CCD [86]. Pathogens in the microbiotic environment in which organisms live are also important for health and as selective agents: metabarcoding of bacterial communities local to European minnow populations has shown that host-parasite interactions drive local adaptation of the major histocompatibility complex (MHC) class IIB loci, in relation to local pathogen diversities [95].…”
Section: Potential For Development Of Edna Methods In Parasitologymentioning
confidence: 99%
“…Collin et al . () also found that DAB1 and DAB3 were driven by different aspects of pathogen‐mediated selection. Specifically, selection favoured different DAB1 alleles in each population suggesting local adaptation to bacterial pathogens, and at DAB3 there was a correlation between genetic diversity and local pathogen diversity.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, genetic differentiation of DAB3 was decoupled from neutral loci and Collin et al . () suggested that bacteria (and not parasites) were the main selective agent on DAB3.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies on cyprinids have shown strong positive selection on the second exon of the DAB3 locus (e.g., Collin, Burri, Comtesse, & Fumagalli, 2013;Ottová et al, 2005;Seifertová & Šimková, 2011), and whether DAB1 or DAB3 loci were more variable differed among species. In the North American Rio Grande silvery minnow (Hybognathus amarus), DAB1 had considerably more allelic diversity, with 55 alleles identified for DAB1 and only 13 alleles identified for DAB3 in a sample of 252 individuals (Osborne et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…A higher number of DAB3 than DAB1 alleles were also found in native ( Parachondrostoma toxostoma ) and invasive ( Chondrostoma nasus ) cyprinids in southern France; 42 DAB3 and 13 DAB1 alleles were identified in the native species (119 individuals), and 23 DAB3 and 6 DAB1 alleles were identified in the invasive species (89 individuals) (Šimková et al., ). In a European minnow ( Phoxinus phoxinus ), DAB3 had greater amino acid diversity than DAB1 at the putative peptide‐binding region (Collin et al., ). In a study comparing 11 species of cyprinid (four to seven individuals per species), a comparable number of DAB1 and DAB3 alleles (40 and 42, respectively) were identified, with up to two DAB3 alleles per individual.…”
Section: Discussionmentioning
confidence: 99%